IMPLEMENTASI PROGRAM KIOS E-PAKLADI DALAM PELAYANAN ADMINISTRASI KEPENDUDUKAN - Muhammad Azzam Taufiqurrahman (Universitas Bina Taruna Gorontalo, 2023)
This study aims to analyze and describe related to the Implementation of the E-Pak Ladi Kiosk Program in Population Administration Services. The type of research used in this study is qualitative using a descriptive approach. The data collection method used is by reviewing legislation, observation, and interviews. The method of data analysis in this study is using data reduction, then followed by presenting the data and drawing conclusions. The Kiosk E-Pak Ladi program is a position service program that can be done electronically in the management of population administration, such as ID cards, death certificates, birth certificates, transfer documents, and others. Legislation Number 24 of 2013 concerning population administration is a series of structuring and controlling activities in the issuance of population documentation and data through population registration, civil registration, management of population administration information, and utilization of results for public service processes and development in other fields . Implementation of the E-Pak Ludi Program aims to realize population administration services that run effectively and efficiently by optimizing the use of electronic-based government systems. The implementation of the E-PakLadi Kiosk Program presents problems and challenges, especially related to socialization between communities and infrastructure. The results of this study show that the E-PakLadi Kiosk Program in Population Administration Services has been running well in its distribution in various villages in Pasuruan, but it is still not optimal in terms of widespread and even socialization and in terms of infrastructure facilities still need to be developed.